2009
DOI: 10.1002/stem.52
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Stroma-Mediated Wnt/β-Catenin Signal Promoting Self-Renewal of Hematopoietic Stem Cells in the Stem Cell Niche

Abstract: With contrasting observations on the effects of b-catenin on hematopoietic stem cells (HSCs), the precise role of Wnt/b-catenin signals on HSC regulation remains unclear. Here, we show a distinct mode of Wnt/b-catenin signal that can regulate HSCs in a stroma-dependent manner. Stabilization of b-catenin in the bone marrow stromal cells promoted maintenance and self-renewal of HSCs in a contactdependent manner, whereas direct stabilization in hematopoietic cells caused loss of HSCs. Interestingly, canonical Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 54 publications
6
79
0
3
Order By: Relevance
“…In the present studies of HSCs, Wnt/b-catenin signaling was suggested to be critical for cellular survival and development [25,26]. In stem cells, Wnt signaling pathways have diverse functions [27].…”
Section: Discussionmentioning
confidence: 75%
“…In the present studies of HSCs, Wnt/b-catenin signaling was suggested to be critical for cellular survival and development [25,26]. In stem cells, Wnt signaling pathways have diverse functions [27].…”
Section: Discussionmentioning
confidence: 75%
“…Canonical Wnts are present in the bone marrow microenvironment and constitute a pivotal group of molecules controlling HSC cell proliferation and differentiation. Recently, Kim et al reported activation of canonical Wnt signaling in the endosteal stroma of bone marrow by systemic injection of Wnt3a (Kim et al, 2009, Oh, 2010. Down-regulation of CXCL12 by canonical Wnt signaling in stroma may therefore play a role in regulating HSC and progenitor mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Kim et al (2009) reported that the population of canonical Wnt receptor molecules and β-catenin accumulation were predominantly enriched in the stromal rather than the hematopoietic compartment of bone marrow (Kim et al, 2009). Therefore, we investigated the role of canonical Wnt function in bone marrow stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for these conflicting observations remain unclear at present. However, we recently showed that distinct biological outcomes can be caused by wnt/b-catenin signals depending on the target site of their activation, that is, while the direct stabilization of bcatenin in HSCs resulted in the loss of their repopulating activity, stabilization in the stroma led to the enhanced selfrenewal of HSCs through cross-talk between the stroma and HSCs in a manner that was dependent on notch signal activation in HSCs [38]. Importantly, endosteal N-cadherin þ osteoblasts exhibited the selective activation of b-catenin under physiological conditions for stimulating hematopoiesis, indicating the physiological relevance of Wnt/b-catenin signals in the stroma [38].…”
Section: Wnt/ß-catenin Signalingmentioning
confidence: 99%
“…However, we recently showed that distinct biological outcomes can be caused by wnt/b-catenin signals depending on the target site of their activation, that is, while the direct stabilization of bcatenin in HSCs resulted in the loss of their repopulating activity, stabilization in the stroma led to the enhanced selfrenewal of HSCs through cross-talk between the stroma and HSCs in a manner that was dependent on notch signal activation in HSCs [38]. Importantly, endosteal N-cadherin þ osteoblasts exhibited the selective activation of b-catenin under physiological conditions for stimulating hematopoiesis, indicating the physiological relevance of Wnt/b-catenin signals in the stroma [38]. A similar insight into the stromal effects of b-catenin arose from studies involving the inducible disruption of b-catenin in the stroma, where co-culturing HSCs with b-catenin null stroma caused a significant decrease in the maintenance of hematopoietic progenitors or spleen colonies (CFU-S) [39].…”
Section: Wnt/ß-catenin Signalingmentioning
confidence: 99%